Trade in services: Opening markets to create opportunities - Bernard M. Hoekman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper reviews the role of services in development and growth, the potential role of trade in services as a driver of the productivity performance of sectors that use services as inputs, and the links between services policies and domestic trade costs. Barriers to trade in services have direct as well as indirect effects on cross-border trade and investment, but research suggests that the extent to which countries will benefit from open services regimes and regional integration of services markets depends on complementary efforts to improve economic governance and regulatory regimes.
Keywords: F13; F15; F23; O24; 330; services; productivity; growth; regional integration; Africa